The Predictive Effects of Family and Individual Wellbeing on University Students' Online Learning During the COVID-19 Pandemic - Zhu, Xiaoqin; Chu, Carman K. M.; Lam, Yee Ching (Frontiers in Psychology, 2022)
The COVID-19 pandemic has significantly changed university students’ life routines, such as prolonged stay at home and learning online without prior preparation. Identifying factors influencing student online learning has become a great concern of educators and researchers. The present study aimed to investigate whether family well-being (i.e., family support and conflict) would significantly predict university students’ online learning effectiveness indicated by engagement and gains. The mediational role of individual well-being such as life satisfaction and sleep difficulties was also tested. This study collected data from 511 undergraduate students (Mean age = 20.04 ± 1.79 years, 64.8% female students) via an online survey. Structural equation modeling analysis revealed positive effects of family support on students’ learning engagement and gains through the mediational effects of life satisfaction and sleep difficulties. In contrast to our expectation, family conflict during the pandemic also positively predicted students’ learning gains, which, however, was not mediated by individual well-being. The findings add value to the existing literature by delineating the inter-relationships between family well-being, individual well-being, and online learning effectiveness. The study also sheds light on the unique meaning of family conflict, which needs further clarification in future studies.